Association between nurses’ coping strategies and their gender and workplace in Jahrom - Golestan Gahromi, Fatemeh; Sayehmiri, Kourosh; Khajavikhan, Javaher; Peyman, Hadi; Safari, Mehdi (Advances in Nursing & Midwifery, 2014)
Abstract Background: Assessing coping strategies of nurses has an important role in determination of nurses and clients’ needs and resolving their problems. The current study aimed to examine the association among nurses’ coping strategies and their gender and workplace in Jahrom hospitals. Material and Methods: A descriptive correlational study, in which 158 nurses were recruited using stratified sampling method was conducted in Jahrom hospitals in 2011. The Lazarus and Folkman coping strategies standard questionnaire was used for data collection. Data were analyzed by SPSS software version 19. Results: More than one-third of participants (41.1%) were male and 11.3% worked in Emergency departments. The mean score of distancing strategy and Seeking Social Support coping was higher in men and women, respectively (P<0.000 for both). There were significant relationship among self-controlling, accepting responsibility, escape-avoidance, plan full problem solving, positive reappraisal and seeking social support coping with workplace of nurses (p<0.01), there was no significant correlation among Confronted and Distancing Coping mechanisms and workplace. Conclusion: Gender and workplace were found to be associated with coping strategies of nurses. Key words: Stress, Coping strategies, nurses